Pengaruh Model Contextual Teaching and Learning Terhadap Hasil Belajar Pada Pembelajaran IPS di Kelas V SD N Gugus 3 Sungai Geringging Ka. Pariaman - Destha, Dwi Ulfira; Yunisrul, Yunisrul; Miaz, Yalvema (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is motivated by the fact that teachers tend to apply the conventional learning model. Learning is still centered on the teacher, so the students less actively participate in the learning. Teachers rarely build basic knowledge of students at the beginning of learning and rarely do reflections at the end of learning, as well as student learning outcomes in IPS lessons that still tend to be under the KKM. This study aims to determine the effect of Contextual Teaching and Learning (CTL) learning on student learning outcomes in learning IPS class V in SD N Gugus 3 Kec. Geringging River Kab.Pariaman in the even semester of the academic year 2017/2018. This research was conducted on the material of figures during the Hindu-Buddhist and Islam in Indonesia.               This research is a quantitative research with experimental type and quasi experimental research design. Sampling data is collected by Random Sampling cluster technique. The sample of this study amounted to 28 people, with a population of 150 people.Based on the research that has been done, obtained t count> ttable = (9,59> 1,70562)> from 0,227 with α = 0,05 means Ho rejected. The average learning outcomes measured by posttest after the learning that is in the experimental class 82.85 and control class 75.14 so that Ha accepted that there is influence the use of Contextual Teaching and Learning (CTL) model of student learning outcomes in learning IPS class V in SD N Gugus 3 Kec. Geringging River Kab.Pariaman.    Keywords: CTL, learning outcomes, IPSThis research is motivated by the fact that teachers tend to apply the conventional learning model. Learning is still centered on the teacher, so the students less actively participate in the learning. Teachers rarely build basic knowledge of students at the beginning of learning and rarely do reflections at the end of learning, as well as student learning outcomes in IPS lessons that still tend to be under the KKM. This study aims to determine the effect of Contextual Teaching and Learning (CTL) learning on student learning outcomes in learning IPS class V in SD N Gugus 3 Kec. Geringging River Kab.Pariaman in the even semester of the academic year 2017/2018. This research was conducted on the material of figures during the Hindu-Buddhist and Islam in Indonesia.               This research is a quantitative research with experimental type and quasi experimental research design. Sampling data is collected by Random Sampling cluster technique. The sample of this study amounted to 28 people, with a population of 150 people.Based on the research that has been done, obtained t count> ttable = (9,59> 1,70562)> from 0,227 with α = 0,05 means Ho rejected. The average learning outcomes measured by posttest after the learning that is in the experimental class 82.85 and control class 75.14 so that Ha accepted that there is influence the use of Contextual Teaching and Learning (CTL) model of student learning outcomes in learning IPS class V in SD N Gugus 3 Kec. Geringging River Kab.Pariaman.    Keywords: CTL, learning outcomes, IPS